Ecological Description of Nematofauna of Annual Weeds - E. Q. Abduraxmonova (Euro Asian Journal Publishing, 2024)
Ecological description of nematoda fauna of annual wild grasses information is provided. Saprobiotic nematodes and A.A. Ecologically divided groups were mentioned by Paramanov
Keywords: ecological classification of phytohelminths; eusaprobionts